Uma introdução aos primos gêmeos: caracterizações e ilustrações - Coelho, Joao Eugenio Camilo (2021)
The present work considers different properties and characterizations of the twin primes numbers. This dissertation will present proofs of specific propositions and theorems from number theory, as well as examples, that elucidate the study of twin prime numbers. In addition, it will be presented the relationships between twin prime numbers and binomial numbers, as well as the reltionship with Fermat’s Little Theorem. The characterization of twin prime numbers and the Clement’s Congruence will be used to obtain twin primes and to present numerical illustrations of the series of reciprocals of primes and twin prime reciprocals, using computational resources as MAXIMA and Python.